Analisis Peluang Curah Hujan Untuk Penetapan Pola Dan Waktu Tanam Serta Pemilihan Jenis Komoditi Yang Sesuai Di Desa Masbagik Kecamatan Masbagik Kabupaten Lombok Timur: Analysis on Rainfall Probability for Determine Pattern and PlantingPeriodand Selection of Appropriate Commodity at Masbagik Village in Masbagik District East Lombok - Iga Dainty; Sirajuddin H. Abdullah; Asih Priyati (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Climatic factor, such as rainfall, greatly contributes to the availability of water for crops. Farmers set a schedule and cropping patterns based on habits, such as the period of rainy month. This method is lack precision on determining crops pattern and often increasing the risk of crop failure. This study aims to determine rainfall probability in Masbagik village on growing season of 2015-2016. Research method was descriptive analytical method. Results of this research revealed that the general rainfall pattern of the study area was still following general pattern of the previous year. Rain probability that approached natural precipitation at the field of study was 50%, with the highest limits at December by 304.5 mm and the lowest at October by 37 mm, while general rainfall probability was normal. Rainy season was predicted to start at mid-November and end at early June, while dry season occurs from early May and end in early November. Recommended scenario of the first growing season for the crop is starting at mid-November until the end of February and the second growing season start at mid-March until June 2015. Moreover, planting time for growing rice can be carried out at mid-October, while from early March growing crops is more suitable.